IMPLEMENTATION OF THE TRAFFIC CONFLICT TECHNIQUE METHOD AT PONTIANAK'S UNSIGNALIZED INTERSECTION - Irwandi, Irwandi; Mukti, Elsa Tri; Sumiyattinah, Sumiyattinah (Fakultas Teknik Universitas Tanjungpura, 2023)
The high number of traffic accidents is a problem for the government in realizing traffic security, safety, and smoothness. Intersections are the most common point of conflict, especially unsignalized intersections. The research location of the intersection of Jl. Budi Utomo - Jl. 28 October-Jl. Parit Nenas, Siantan Hulu Village, North Pontianak District, and Pontianak City intersect environmental-type commercial roads with many vehicles and education centers. The research objectives are to identify traffic conflicts, analyze the level of traffic conflicts, and provide alternatives to overcome problems.Traffic Conflict Technique is an observation method to analyze traffic conflict that illustrates the seriousness of the conflict. The research data used CCTV recording for two days, Saturday and Tuesday. The Traffic Conflict Technique method uses the Time to Accident and Conflicting Speed values to determine the seriousness of the conflict.Based on the analysis of the Traffic Conflict Technique method, the research location with 34 vehicle conflicts has a severe level of conflict that could potentially cause accident risk. The level of serious conflict is 27 vehicle conflicts, with a percentage of 79.41%. Vehicle speed in the class 15 km / h - 19 km / h is the most severe conflict speed, with 12 vehicle conflicts and a percentage of 44.44%. Accelerating vehicle behavior is the most severe conflict, with 25 vehicle conflicts and a percentage of 83.33% of accidents that have the potential to occur. Alternatives to reduce the causes of accidents are adding traffic signaling devices and traffic signs to improve safety.